HUBUNGAN PERSONAL HYGIENE IBU RUMAH TANGGA DENGAN KEJADIAN SKABIES DI LINGKUNGAN V KELURAHAN SIRANTAU KECAMATAN DATUK BANDAR KOTA TANJUNGBALAI TAHUN 2019: Nama Lengkap Penulis : Erlina Esther Rotua Siringoringo,SST,MKM - Erlina Esther Siringo ringo (Media LPPM Sehati, 2020)
Scabies is a skin disease caused by Sarcoptes scabiei mite variant infestation and sensation and its products on the body are also called the itch, seven year itch, Norwegian itch, scabies, agogo itching, amusement and ampera disease. Scabies is a zoonotic disease that attacks the skin, can attack all groups throughout the world. This type of research is an analytical survey with cross sectional research design, with the aim to find out the relationship of personal hygiene of housewives with the incidence of scabies in Environment V of Sirantau Sub-District of Datuk Bandar Kota Tanjungbalai in 2019. The number of samples in this study were 54 housewives respondent. The sampling technique uses the Random Sampling method. Data were analyzed using chi square test and exact fisher. The results showed that the majority of poor personal hygiene were 44 (81.5%) and the majority were suffering from scabies 31 (57.4%). There is no relationship between personal hygiene with the incidence of scabies with p = 0.052 ≤ 0.05. The results of statistical analysis using the Chy square test obtained p value of 0.052 having expected count value <5 obtained p value> 0.05. It is suggested to respondents to improve personal hygiene and the role of health workers in improving services and community empowerment in the prevention of scabies